The relationship of some forms of motor coordination to the accuracy of serving and hitting high aces in youth volleyball - Ahmed Hassan Saber Al Kaabi, (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Introduction: A volleyball player must possess the ability of motor coordination in order to help move quickly and powerfully on the court while executing the skill of serving and hitting aces. The researcher observed that there is a clear weakness in the level of accuracy of the technical performance of the two offensive skills by most of the players of the participating teams. The aim of the research is to identify the relationship between some forms of motor coordination and the accuracy of the performance of serving and hitting high aces in youth volleyball. Research hypotheses: There is a statistically significant correlation between some forms of motor coordination and the accuracy of the performance of the skills of serving and hitting high aces in youth volleyball. Research methodology and field procedures: The researcher used the descriptive method with a correlational approach. The research community is represented by the players of Qatar's youth volleyball clubs, and the research sample is the players of Naft Maysan youth volleyball club and their number (12) players who participated in the game league for the season (2024). Conclusions The results showed that there is a statistically significant correlation between motor coordination (strength characterized by speed, flexibility and motor coordination) and the accuracy of the performance of the skill of high aces among youth volleyball players. Recommendations Emphasize the importance of developing the ability of motor coordination in the stages of preparation in general and the youth category in particular, due to its importance in the accuracy of performing the skills of serving and hitting high aces in youth volleyball.